THU0237 First-in-Human Study of Vagus Nerve Stimulation for Rheumatoid Arthritis: Clinical and Biomarker Results Through Day 84. (23rd January 2014) - Koopman, F.; Miljko, S.; Grazio, S.; Sokolovic, S.; Tracey, K.; Levine, Y.; Zitnik, R.; Tak, P.-P.
Abstract : Background: The inflammatory reflex regulates innate and adaptive immunity. Activation of its efferent arm (the Cholinergic Anti-inflammatory Pathway (CAP)), by electrical vagus nerve stimulation (VNS) reduces systemic inflammation and ameliorates disease in many acute and chronic animal models 1 . Objectives: We determined whether VNS could improve clinical manifestations and biomarkers of inflammation in rheumatoid arthritis (RA). Methods: This is an open label study of patients with active RA (>/= 4 tender and 4 swollen joints, and CRP at least 7 mg/L) despite stable methotrexate for 3 months. After a pre-implantation baseline visit, patients were surgically implanted with a Cyberonics VNS system. The device delivered the first VNS during its standard intraoperative diagnostic check sequence. Two weeks after implantation, patients returned for initial in-clinic VNS. Treatment continued through the primary endpoint at Day 42, was withdrawn for a 14-day hiatus, reinitiated at day 56, and then maintained through the final day 84 visit. Biomarker assessments including serum cytokine levels, FACS of circulating cell markers, and whole blood in vitro LPS-stimulated TNF release were performed. Results: 8 patients (7/8 RF+, 6/8 ACPA+) were enrolled. Implantation and stimulation were generally well tolerated. Moderate postoperative hoarseness occurred in one patient. ACR 20/50/70 responses at the day 42 primary endpoint were 75, 50, and 25%, respectively. During the 14-day treatment withdrawal period after day 42, the mean DAS28 worsened significantly (+0.95, 95% CI 0.15-1.75). After treatment re-initiation at day 56, the ACR 20/50/70 responses at the day 84 final visit were 62.5, 25, and 12.5%, respectively. Circulating CD25+FoxP3+Tregs were increased by 31%, and whole blood in vitro LPS-stimulated TNF release was reduced by 59% at day 42 compared with pre-implantation baseline values. In patients with a day 42 EULAR response, serum IL-6 was reduced by 56%. Conclusions: VNS was generally well tolerated and improved signs and symptoms of RA. Treatment withdrawal was associated with worsening, and re-initiation with improvement in disease activity. Clinical improvement was associated with reduction in important mediators of systemic inflammation, increases in circulating T regulatory cells and decrease in the ability of circulating leukocytes to release TNF in response to endotoxin. These improvements in objective biomarkers were consistent with effects observed in preclinical inflammation models using VNS. This is the first demonstration in humans that stimulation of the CAP can favorably impact clinical manifestations of systemic inflammation. If efficacy and safety are confirmed in larger controlled studies, implantable medical devices may offer a feasible alternative approach to the treatment of RA and other chronic inflammatory diseases. References: Andersson U, Tracey K, Annu. Rev. Immunol. 2012; 30:313 Disclosure of Interest: F. Koopman: None Declared, S. Miljko Grant/research support from: SetPoint Medical, S. Grazio Grant/research support from: SetPoint Medical, S. Sokolovic Grant/research support from: SetPoint Medical, K. Tracey Shareholder of: SetPoint Medical, Consultant for: SetPoint Medical, Y. Levine Shareholder of: SetPoint Medical, Employee of: SetPoint Medical, R. Zitnik Shareholder of: SetPoint Medical, Employee of: SetPoint Medical, P.-P. Tak Grant/research support from: SetPoint Medical, Consultant for: SetPoint Medical